Integrated 3D imaging of FFPE lung tissue combining microCT, light and electron microscopy allows for contextualized ultrastructural and histological analysis - Reiser, Johanna; Albers, Jonas; Svetlove, Angelika; Mertiny, Mara; Kommoss, Felix; Schwab, Constantin; Schneemann, Anna; Tromba, Giuliana; Wacker, Irene; Curticean, Ernest Ronald; Schröder, Rasmus R.; Kauczor, Hans-Ulrich; et al. (Scientific reports, 2025)
Classical histopathology of formalin fixed and paraffin embedded (FFPE) tissue using light microscopy (LM) remains the undisputed gold standard in biomedical microstructural lung tissue analysis. To extend this method, we developed an integrative imaging and processing pipeline which adds 3D context and screening capabilities by microCT (µCT) imaging of the entire paraffin block and adds ultrastructural information by correlative same-slide scanning electron microscopy (SEM). The different modalities are integrated by elastic registration to provide hybrid image datasets. Without compromising standard light microscopic readout, we overcome the limitations of conventional histology by combining and integrating several imaging modalities. The biochemical information contained in histological and immunohistological tissue staining is embedded into the 3D tissue configuration and is amplified by adding ultrastructural visualization of features of interest. By combining µCT and conventional histological processing, specimens can be screened, and specifically preselected areas of interest can be targeted in the subsequent sectioning process. While most of the µCT data shown in the manuscript was acquired at a Synchrotron, we further demonstrate that our workflow can also be applied using X-ray microscopy.
Gesehen am 17.09.2025